How trade-offs between ecological construction and urbanization expansion affect ecosystem services - Chuxiong Deng (Elsevier, 2021)
The trade-offs between ecological construction and urbanization changes in land-use, which can affect ecosystem services. This study aimed to analyze the trade-offs between urbanization and ecological construction through land-use change, and then to explore its impact on ecosystem services. We developed a coefficient for analyzing LUCC caused by ecological construction and urbanization. The spatio-temporal patterns of three ecosystem services (Water yield, Net primary production, Soil conservation) in the Xiangjiang River Basin (XRB) of China were identified and the trade-offs and synergies between ecosystem services explored at different spatial scales. The average trade-off coefficients between ecological construction and urbanization of upstream, midstream, downstream, and the whole basin were 0.20, −0.27, −0.46 and −0.37 respectively show that the LUCC was dominated by urbanization in the XRB from 2000 to 2015. However, ecological construction improved ecosystem services. The growth rates in NPP, soil conservation, and water yield were 10.88%, 2.23%, and 19.82%, respectively, between 2000 and 2015. We also confirmed three ecosystem services were spatially dominated by synergies (0<R<0.3, p<0.01). Temporally, three ecosystem services went from negative synergy or trade-off to positive synergy. Consequently, our results indicate that the trade-off between within reasonable range ecological construction and urbanization does not mean ecosystem services inevitably decline at the whole basin scale. However, land-use planning and policy making for rapidly urbanizing regions should take ecosystem services into account to preserve natural ecosystems.